Multifunctional MXene/Carbon Nanotube Janus Film for Electromagnetic Shielding and Infrared Shielding/Detection in Harsh Environments - Hassan, Tufail; Iqbal, Aamir; Yoo, Byungkwon; Jo, Jun Young; Cakmakci, Nilufer; Naqvi, Shabbir Madad; Kim, Hyerim; Jung, Sungmin; Hussain, Noushad; Zafar, Ujala; Cho, Soo Yeong; Jeong, Seunghwan; et al. (Nano-Micro Letters, 2024)
Multifunctional, flexible, and robust thin films capable of operating in demanding harsh temperature environments are crucial for various cutting-edge applications. This study presents a multifunctional Janus film integrating highly-crystalline Ti3C2Tx MXene and mechanically-robust carbon nanotube (CNT) film through strong hydrogen bonding. The hybrid film not only exhibits high electrical conductivity (4250 S cm−1), but also demonstrates robust mechanical strength and durability in both extremely low and high temperature environments, showing exceptional resistance to thermal shock. This hybrid Janus film of 15 μm thickness reveals remarkable multifunctionality, including efficient electromagnetic shielding effectiveness of 72 dB in X band frequency range, excellent infrared (IR) shielding capability with an average emissivity of 0.09 (a minimal value of 0.02), superior thermal camouflage performance over a wide temperature range (− 1 to 300 °C) achieving a notable reduction in the radiated temperature by 243 °C against a background temperature of 300 °C, and outstanding IR detection capability characterized by a 44% increase in resistance when exposed to 250 W IR radiation. This multifunctional MXene/CNT Janus film offers a feasible solution for electromagnetic shielding and IR shielding/detection under challenging conditions. Highlights: 1 A multifunctional Janus film is fabricated by integrating highly-crystalline and oxidation-resistant Ti3C2Tx MXene with carbon nanotube (CNT) film through strong hydrogen bonding, which exhibits high electrical conductivity of 4250 S cm−1 and robust mechanical strength of 77 MPa. 2 The MXene/CNT Janus film of 15 μm thickness demonstrates efficient electromagnetic interference shielding of 72 dB, low infrared (IR) emissivity of 0.09 and hence superior thermal camouflage performance, and outstanding IR detection capability, while maintaining its integrity equally at room temperature as well as under extreme conditions. 3 This multifunctional MXene/CNT Janus film offers a practical solution for electromagnetic shielding and IR shielding/detection in challenging conditions.